(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Feasibility Analysis of Shallot Farming in Merta Jaya Livestock Farmer Group Songan B Village Kintamani District Bangli Regency. Many farmers are cultivating the shallot commodity as their main source of livelihood. Farmers’ shallot farming activities will also consider costs and income. The purpose of this study was to determine the income of shallot farming and the feasibility of shallot farming in the Merta Jaya Livestock Farmer Group, Songan B Kintamani Village. Data collection methods used are observation, interviews, and library research. Based on the results of research at the Merta Jaya Livestock Farmers Group, Songan B Village, Kintamani District, Bangli Regency, it can be concluded as follows. The average amount of income received by farmers in shallot farming in the Merta Jaya Livestock Farmers Group is Rp 26,019,271. This can be seen from the revenue generated, which is IDR 42,320,000, with a production cost of IDR 16,300,729 which consists of fixed costs and variable costs. Average income, revenue and production costs with a land area of 44,35 acres, the planting season is June-August. The results of the feasibility analysis using the R/C ratio analysis show that shallot farming in the Merta Jaya Livestock Farmers Group is feasible. It can be seen that the value of the R/C ratio is more than 1, namely 3, where the revenue is greater than the cost. Based on the conclusion of the suggestions that can be given to the Merta Jaya Livestock Farming Group, it is better for the Farmer Group to optimize jointly owned land so that it can be used for savings and loan capital without giving interest to group members.